Menuju Manajemen Talenta Sektor Publik: Faktor yang Memengaruhi, Tantangan, dan Strategi - Seno, Ramadhani Haryo (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2022)
Focus of this research was to describe of talent management in public sector, especially influencing factors, challenges, and strategies. This research applied descriptive qualitative analysis by combining library research and examining secondary data. There were four factors that played as influence, challenge, and strategy in talent management implementation for public sector, i.e. (1) cultural, (2) human resource, (3) managerial/structural, and 4) environmental. Cultural factor included making sustainable talent management.Â Human resource included capability, passion, and program performance measurement. Managerial factor included leadership, organizational commitment, and activists were needed in implementing TM consistently. Environmental factor included regulation, budget, and political support on the national scale.